(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: This study on the epidemiology of lung cancer in Hanoi from 2015 to 2019 offered crucial details on the situation of the disease and epidemiological characteristics of lung cancer. Methods: Data was collected retrospectively in a descriptive study with analysis. Results: In Hanoi, 7389 new cases of lung cancer were diagnosed between 2015 and 2019. In which, the age group 70-79 had the highest new incidence rate of age-specific lung cancer (116.2 cases/100.000 population).The crude incidence rate was 20.3/100.000; the age-standardized incidence rate was 19.6/100.000 (with 31.6/100.000 for males and 9.7/100.000 for females); and the age-standardized incidence rate in the inner city was lower (13.7/100.000) than that in the suburban area (19.4/100.000). Conclusion: Lung cancer was still a public health issue that required special attention. Effective tobacco control initiatives, early detection screening, and improved treatment quality were the top priorities for reducing the negative effects of lung cancer in the community.